Hola mates !
Answer 5 iii) ...
Attachments:
![](https://hi-static.z-dn.net/files/dab/0a0aee70361cfb50f30a73199098dc21.jpg)
Answers
Answered by
4
Hi
Here is your answer
Answer:
= 17 / 7
Step-by-step explanation:
X = 2
Y = 3
Z = - 1
= (2x + 3y - 4z)/3x - z
= (2 × 2 + 3 × 3 - 4 × ( - 1 ))/ 3×2 - (-1)
= (4 + 9 + 4 ) / 6 + 1
= (8 + 9) / 7
= 17 / 7
Hope it helps You
Answered by
6
see attached file to your question
Attachments:
![](https://hi-static.z-dn.net/files/d20/9602f8b21703d0721cbff53761c2e0a1.jpg)
Similar questions